Evolutionary modeling and correcting for observation error support a 3/5 brain-body allometry for primates. Issue 94 (May 2016) - Grabowski, Mark; Voje, Kjetil L.; Hansen, Thomas F.
Abstract: The tight brain-body allometry across mammals and primates has motivated and informed many hypotheses about brain evolution in humans and other taxa. While a 2/3 or a 3/4 scaling is often at the core of such research, such exponents are derived from estimates based on particular statistical and evolutionary assumptions without careful consideration of how either may influence findings. Here we quantify primate brain-body allometry using phylogenetic comparative methods based on models of both adaptive and constrained evolution, and estimate and account for observational error in both response and predictor variables. Our results supported an evolutionary model in which brain size is directly constrained to evolve in unison with body size, rather than adapting to changes in the latter. The effects of controlling for phylogeny and observation error were substantial, and our analysis yielded a novel 3/5 scaling exponent for primate brain-body evolutionary allometry. Using this exponent with the latest brain- and body-size estimates to calculate new encephalization quotients for apes, humans, and fossil hominins, we found early hominins were substantially more encephalized than previously thought.